Análisis del uso de infografía del medio de comunicación mexicano "Pictoline" - Santos Andrade, Víctor Ismael (2023)
The case study called: “Analysis of the use of infographics of the Mexican media "Pictoline", has the general objective of determining the use of infographics of the digital media Pictoline, to know what benefits it brings to society.; To carry out and obtain results of this state, the explanatory research method was used hand in hand with descriptive research and techniques for obtaining information such as direct observation using a sheet to determine the theory of recognized authors that helps understanding. about the topic; In the same way, the content analysis of the infographics presented on the different media platforms was used; Regarding the fundamental elements that must be met to be of quality, authors referring to this topic were cited, giving rise to a knowledge base for carrying out our observation technique in an assertive and critical manner. It was observed that in the organization of the content published by the digital medium Pictoline, quality of information, individuality, which generates a positive impact on the reading community, which is why they tend to share them on their social networks, a situation that helps to improve the comunication system.